Dicto-Comp: A technique in reducing high school students’ errors in writing - Rosdiana Rosdiana (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2020)
This study investigated the use of dicto-comp in minimizing errors in students’ writing. The study concerned the type of errors frequently made by the students after the implementation of dicto-comp and the effectiveness of dicto-comp in reducing the students’ errors in writing. The study used the quantitative approach using the quasi-experimental research design. The instrument of the study was writing tests. The study took place at a senior high school in Banda Aceh, Aceh Province, Indonesia. Findings showed that after the implementation of dicto-comp, the students frequently made grammatical errors at 46.42% and mechanical errors at 40.66%. Further, the t-test results showed that t-test = 2.12 and t-table = 1.70. This indicated that t-test score was higher than t-table, and thus, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Therefore, it can be concluded that dicto-comp decreased the errors in the students’ writing. It is suggested that teachers of English apply dicto-comp technique and/or combine it with another method/ strategy in teaching writing in classroom